Photo of group with Margaret Bennett - Bennett, Margaret (2009)
Group photo of 15 individuals, including Margaret Bennett on far right in the back row, with several other individuals in the background. Several people are wearing tartan (some Newfoundland Tartan) and four are holding instruments, three guitars and an accordian.